Selective extraction of chicahuastle: effects, local knowledge, and management guidelines - Palacios-Wassenaar, Olivia M.; Castillo-Campos, Gonzalo; Vázquez-Torres, Mario; Wojtarowski, Astrid (Instituto de Ecología, A.C., 2022)
The chicahuastle (Stenostomum aromaticum) is an endemic tree of the semi-deciduous forest in the center of Veracruz, Mexico, in danger of extinction due to its restricted distribution, timber use, and destruction of its habitat. The effect of selective extraction on the diameter and height of individuals and population density was evaluated, as well as the perception of local people about the species, to propose management guidelines. Individuals of S. aromaticum and their population density were evaluated in five sites with the presence of this species, and surveys and semi-structured interviews were conducted with residents in Jalcomulco, Veracruz. The extraction consists of cutting branches of a specific size; this procedure does not generate evident alteration on the diameter, but it does on the height of the individuals. Its high regrowth capacity and its persistence in fragments of preserved primary vegetation have contributed to the survival of this species. It is concluded that selective extraction affects the vertical growth of the species, with possible adverse effects for the long-term survival of the species; and that the population density was reduced. Knowledge about this species is concentrated in older peasants while young people are unaware of its existence and uses, so this knowledge is at risk of being lost if its dissemination is not promoted. The creation of a reserve, and the community management of the species are the most accepted measures among local people for its conservation.